Scale Adaptation in Organizational Science Research: A Review and Best-Practice Recommendations - Heggestad, Eric D.; Scheaf, David J.; Banks, George C.; Monroe Hausfeld, Mary; Tonidandel, Scott; Williams, Eleanor B. (Journal of Management, 2019)
In describing measures used in their research, authors frequently report having adapted a scale, indicating that they changed something about it. Although such changes can raise concerns about validity, there has been little discussion of this practice in our literature. To estimate the prevalence and identify key forms of scale adaptation, we conducted two studies of the literature. In Study 1, we reviewed the descriptions of all scales ( N = 2,088) in four top journals over a 2-year period. We found that 46% of all scales were reported by authors as adapted and that evidence to support the validity of the adapted scales was presented in 23% of those cases. In Study 2, we chose six scales and examined their use across the literature, which allowed us to identify unreported adaptations. We found that 85% of the administrations of these scales had at least one form of adaptation and many had multiple adaptations. In Study 3, we surveyed editorial board members and a select group of psychometricians to evaluate the extent to which particular adaptations raised concerns about validity and the kinds of evidence needed to support the validity of the adapted scales. To provide guidance for authors who adapt scales and for reviewers and editors who evaluate papers with adapted scales, we present discussions of several forms of adaptations regarding potential threats to validity and recommendations for the kinds of evidence that might best support the validity of the adapted scale (including a reviewer checklist).